Functional characterization of the novel DES mutation p.L136P associated with dilated cardiomyopathy reveals a dominant filament assembly defect. (February 2016) - Brodehl, Andreas; Dieding, Mareike; Biere, Niklas; Unger, Andreas; Klauke, Bärbel; Walhorn, Volker; Gummert, Jan; Schulz, Uwe; Linke, Wolfgang A.; Gerull, Brenda; Vorgert, Matthias; Anselmetti, Dario; et al.
Abstract: Background: Dilated cardiomyopathy (DCM) could be caused by mutations in more than 40 different genes. However, the pathogenic impact of specific mutations is in most cases unknown complicating the genetic counseling of affected families. Therefore, functional studies could contribute to distinguish pathogenic mutations and benign variants. Here, we present a novel heterozygous DES missense variant (c.407C > T; p.L136P) identified by next generation sequencing in a DCM patient. DES encodes the cardiac intermediate filament protein desmin, which has important functions in mechanical stabilization and linkage of the cell structures in cardiomyocytes. Methods and results: Cell transfection experiments and assembly assays of recombinant desmin in combination with atomic force microscopy were used to investigate the impact of this novel DES variant on filament formation. Desmin-p.L136P forms cytoplasmic aggregates indicating a severe intrinsic filament assembly defect of this mutant. Co-transfection experiments of wild-type and mutant desmin conjugated to different fluorescence proteins revealed a dominant affect of this mutant on filament assembly. These experiments were complemented by apertureless scanning near-field optical microscopy. Conclusion: In vitro analysis demonstrated that desmin-p.L136P is unable to form regular filaments and accumulate instead within the cytoplasm. Therefore, we classified DES -p.L136P as a likely pathogenic mutation. In conclusion, the functional characterization of DES -p.L136P might have relevance for the genetic counseling of affected families with similar DES mutations and could contribute to distinguish pathogenic mutations from benign rare variants. Highlights: Identification of a novel DES variant in a DCM patient using next generation sequencing DES -p.L136P disturbs filament assembly. Co-expression analysis of mutant and wild-type desmin reveals a dominant effect. Classification of DES -p.L136P as a likely pathogenic mutation